The nine : the true story of a band of women who survived the worst of Nazi Germany - Strauss, Gwen (St. Martin's Press, 2021)
The Nine Xi -- Map Of Escape Route Xi I I -- Hélène -- Zaza -- Nicole -- Lon And Guigui -- Zinka -- Josée -- Jacky -- Mena -- The Longest Day -- Return To Life -- Finding The Way Home -- It's Only A Goodbye.